(3GdaSGO CHQR GdLQGFe (B:s (3GdBKGQ hSHd GdeYGdLI (B/s - (3HjVhf, aGOjG bGSes ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2013)
(3jJfGhd cJGH (B"(3GdaSGO CHQR GdLQGFe (B: (3GdBKGQ hSHd GdeYGdLI(B" (3hGdJj bGeJ HJCdjag (B"(3GdOcJhQI aGOjG bGSe HjVhf(B" (3aj MhGdj (B(496) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdLQjeI hGdeLQehf(B)(3, jJfGhd bVjI GdaSGO hChVMJ eYfGg agh dZI GdYUQ eJfhY GdCTcGd eNJda GdChLg GdJj JfcTa MjfG hJNJaj CMjGfG aHYO YQV ChLg GdQThI hGdGNJdGS JhUdJ Edi Cf hLhOg CUHM XGgQI eYJQa HgG aj GdOhd GdZfjI hGdabjQI Ydi MO ShGA jSJWjYGf GdONhd Edi GdEOGQGJ GdYGeI hGdNGUI HSghdI cHjQI(B.s
(3JfVjO hENQGL (B: MECA.s
(3HHdjhLQGajI (B: (3UaMI (B413-486.s
Keywords: (3GdLQjeI hGdeLQehfs -- (3bhGfjf hJTQjYGJs -- (3dHfGfs; (3GdaSGO GdEOGQjs -- (3hbGjIs -- (3bhGfjf hJTQjYGJs -- (3dHfGfs